1997
DOI: 10.1182/blood.v90.9.3776
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of GBV-C/Hepatitis G Virus Infection Through the Follow-Up of GBV-C/Hepatitis G Virus–Infected Blood Donors and Recipients Studied by RNA Polymerase Chain Reaction and Anti-E2 Serology

Abstract: The aims of this study were to determine the outcome and the natural history of GBV-C/hepatitis G virus (HGV) infection and to establish the frequency of acute or persistent infections in multiply-transfused individuals and blood donors. We used a GBV-C/HGV RNA polymerase chain reaction (PCR) and an assay evidencing antibodies to the envelop protein E2, which is considered a marker for virus clearance. Among 16 PCR-positive recipients, 11 were still positive for GBV-C/HGV RNA at the end of the study period; si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 24 publications
5
35
0
1
Order By: Relevance
“…In a study with healthy individuals aged 16-67 years in Uzbekistan, it has also been shown that GBV-C/HGV infection was distributed among younger people [Kato et al, 1997]. The high value (18%) encountered in age group of 21-30 years was likely due to the persistence of GBV-C/HGV infection, commonly for 5-10 years, as previously reported [Lefrère et al, 1997]. Indeed, such a long period of infection increases the probability of viral RNA detection in a cross-sectional study.…”
Section: Discussionsupporting
confidence: 68%
“…In a study with healthy individuals aged 16-67 years in Uzbekistan, it has also been shown that GBV-C/HGV infection was distributed among younger people [Kato et al, 1997]. The high value (18%) encountered in age group of 21-30 years was likely due to the persistence of GBV-C/HGV infection, commonly for 5-10 years, as previously reported [Lefrère et al, 1997]. Indeed, such a long period of infection increases the probability of viral RNA detection in a cross-sectional study.…”
Section: Discussionsupporting
confidence: 68%
“…The clinical relevance of HGV infection is still being debated, because most viremic subjects have normal ALT levels (3)(4)(5)(12)(13)(14). HGV RNA has been detected in some patients with non-A-E fulminant hepatitis (12) or with acute and chronic forms of hepatitis (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Seroconversion to viral proteins is almost always associated with the disappearance of detectable viremia (9)(10)(11), which implies that the humoral immune response usually leads to viral clearance. Although HGV RNA status can cause acute and chronic hepatitis, most viremic subjects tend to have normal levels of alanine aminotransferase (ALT) (3)(4)(5)(12)(13)(14); thus, the real pathogenetic potential of HGV remains uncertain.…”
mentioning
confidence: 99%
“…Like hepatitis C virus (HCV), GBV-C infection is found worldwide and is capable of persistent human infection [8,9]. GBV-C infection is common, and between 1 and 5% of healthy blood donors in developed countries are viraemic at the time of donation.…”
Section: Epidemiology and Disease Associationmentioning
confidence: 99%